高脂肪食およびLPS投与が脳内炎症、神経新生および認知機能に及ぼす影響 - 永田, 亘; 石塚, 俊晶; 佐藤, 泰司; 太田, 宏之; 高橋, さやか (日本薬理学会年会要旨集, 2021)
[Introduction] It is suggested that high fat diet (HFD)-induced brain inflammation, which has an important role in the pathogenesis of Alzheimer’s disease (AD), may be due to TNF secretion from adipose tissues and increased intestinal bacterial lipopolysaccharide (LPS). Previously, we showed that stimulation with TNF and LPS significantly suppressed proliferation and differentiation of neural progenitor cells. Thus, we determined the effects of HFD feeding and LPS treatment on neuroinflammation, neurogenesis, or cognitive function. [Materials and Methods] C57BL/6 mice were fed a normal diet or HFD for 16 weeks and were treated with LPS or vehicle for 5 days. After the treatment, mice were tested in Morris water maze to assess cognitive function. Plasma samples were collected and perfused brain tissues were harvested. Plasma TNF levels were determined using enzyme immunoassay kits. Immunofluorescence staining was performed to assess neuroinflammation and neurogenesis using specific antibodies (Iba-1, IL-1beta, BrdU, etc.). [Results] High fat loading significantly increased plasma TNF levels, which were not affected by LPS treatment. The LPS treatment increased IL-1beta-positive microglial cells and decreased BrdU-positive cells in hippocampus of high fat-loaded mice. However, in Morris water maze test, there was no significant difference in time spent in target zone between all groups. [Conclusion] These results suggest that neuroinflammation and reduced neurogenesis were induced by HFD feeding and LPS treatment, which did not affect cognitive function.